2018
DOI: 10.1038/s41467-017-02536-7
|View full text |Cite
|
Sign up to set email alerts
|

Impaired autophagy bridges lysosomal storage disease and epithelial dysfunction in the kidney

Abstract: The endolysosomal system sustains the reabsorptive activity of specialized epithelial cells. Lysosomal storage diseases such as nephropathic cystinosis cause a major dysfunction of epithelial cells lining the kidney tubule, resulting in massive losses of vital solutes in the urine. The mechanisms linking lysosomal defects and epithelial dysfunction remain unknown, preventing the development of disease-modifying therapies. Here we demonstrate, by combining genetic and pharmacologic approaches, that lysosomal dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
150
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(158 citation statements)
references
References 64 publications
8
150
0
Order By: Relevance
“…We hypothesize that CTNS loss affects lysosomal function by hampering the delivery of newly synthesized lysosomal enzymes from Golgi to lysosomes and/or by inhibiting the maturation of these enzymes within (endo) lysosomal compartments. The latter hypothesis was confirmed by Festa et al where they have shown the impairment of lysosome proteolysis (both in vitro and in vivo) is a result of defective cathepsin activation 13 .…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…We hypothesize that CTNS loss affects lysosomal function by hampering the delivery of newly synthesized lysosomal enzymes from Golgi to lysosomes and/or by inhibiting the maturation of these enzymes within (endo) lysosomal compartments. The latter hypothesis was confirmed by Festa et al where they have shown the impairment of lysosome proteolysis (both in vitro and in vivo) is a result of defective cathepsin activation 13 .…”
Section: Discussionmentioning
confidence: 73%
“…Recently, it has been shown that cystinosin loss-of-function compromises autophagy-mediated clearance of dysfunctional mitochondria, which are the potent source of ROS-producing compounds 13 . In this context, the αKG lowering effect of bicalutamide can be explained by its autophagy-activating properties, where it stimulates cellular exocytosis and restores endocytic cargo processing, leading to a decreased autophagy-mediated ROS production in cystinosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no podocyte damage was present [41]. The latter mouse model has been widely used by different research groups for studying the pathogenesis and treatment strategies in cystinosis [42,43].…”
Section: Mousementioning
confidence: 99%
“…Additionally, autophagy, an evolutionarily conserved mechanism related to cell survival, is involved in CKD [14]. Abnormal autophagy function might be linked to kidney impairments to some extent [15]. A group of Chinese researchers revealed that miR-376b can mediate pathways related to autophagy, and autophagy-related gene 4 (Atg4) can be regulated by miR-376b [16].…”
Section: Introductionmentioning
confidence: 99%